Pakikipagkapwa (Fellowship): Towards an Interfaith Dialogue with the Religious Others - Canete, Jonathan James (Religions, 2022)
The present study examines the ways in which the Filipino Christian value of pakikipagkapwa (fellowship) can be seen and experienced in modern society. Using empirical phenomenology, this paper aims to (re)imagine the ways of cultivating ways of dialogue with religious others while understand the meaning of pakikipagkapwa (fellowship). This study explores the contemporary notions and practices of pakikipagkapwa among select Filipino Christians and how such cultural value fosters interreligious dialogue. Moreover, the study investigates the importance of dialogue between religious actors as they navigate the uncharted waters of the COVID-19 pandemic. The authors contend that pakikipagkapwa and interreligious dialogue build communities, support social cohesion, and help religious actors find meaning in difficult circumstances.